Review of Groundwater Mapping and Water Quality Assessment Using GIS and Water Quality Index (WQI) - Virendrakumar Bhikajirao Patil (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Groundwater is a vital resource for drinking water, agriculture, and industrial use. Accurate mapping and quality assessment of groundwater are crucial for sustainable management and protection against contamination. This review paper synthesizes findings from various studies employing Geographic Information Systems (GIS) and Water Quality Index (WQI) methodologies for groundwater assessment. The review covers the use of these tools in different geographical contexts and highlights their effectiveness in evaluating groundwater potential and quality. The Water Quality Index (WQI) provides a comprehensive measure of water quality by aggregating multiple water quality parameters into a single index value. This facilitates the comparison of water quality across different regions and time periods, and helps in identifying trends and changes in groundwater quality. The application of WQI in groundwater studies has proven effective in guiding water management policies. This paper discusses case studies from diverse geographical areas, showcasing the versatility and applicability of GIS and WQI in groundwater assessment. These examples illustrate how different regions have utilized these tools to address specific groundwater challenges, from resource depletion to contamination threats. Moreover, the paper highlights the integration of GIS and WQI with other advanced technologies, such as remote sensing, which enhances the accuracy and reliability of groundwater assessments. Future research directions are proposed, emphasizing the need for interdisciplinary approaches and the development of more sophisticated models to predict groundwater behaviour under changing environmental conditions.